2009
DOI: 10.1002/adsc.200900631
|View full text |Cite
|
Sign up to set email alerts
|

3,5‐Bis(n‐perfluorooctyl)benzyltriethylammonium Bromide (F‐TEBA): An Efficient, Easily Recoverable Fluorous Catalyst for Solid‐Liquid PTC Reactions

Abstract: A readily available 3,5-bis(perfluorooctyl)benzyl bromide and triethylamine were reacted under mild conditions to give 3,5-bis(n-perfluorooctyl)benzyltriethylammonium bromide (F-TEBA), an analogue of the versatile phase-transfer catalyst, benzyltriethylammonium chloride (TEBA), containing two fluorous ponytails. This perfluoroalkylated quaternary ammonium salt was successfully employed as a catalyst in a variety of reactions run under solid-liquid phase-transfer catalysis (SL-PTC) conditions. Thus, being both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…4 and Table 3 demonstrate clearly that by adding perfluoroalkyl sidearms to the dibenzo-18-crown-6 structure in compounds (14) and (15), the phase transfer catalytic activity is increased significantly, but when alkyl sidearms are attached in compound (11), the catalytic activity only increases moderately compared to dibenzo-18-crown-6 (9). The results also showed that compounds (14) and (15) have essentially the same catalytic activity and so, the length of the perfluoroalkyl group does not affect the catalytic activity in benzotrifluoride. On the other hand, the cis-4,4 0 -dialkylamino crown ether (18) showed extremely poor catalytic activity under the same reaction conditions, whilst the cis-4,4 0 -di(1H,1H-perfluoroalkylamino)-derivatised crown ether (19) had a very similar rate profile to dibenzo-18-crown-6 after 5 h. Presumably, the polarity and solubility of (18) had an important effect on the reaction equilibria constants in benzotrifluoride and (18) may be a more efficient PTC catalyst in an alternative non-fluorinated organic solvent.…”
Section: Phase Transfer Catalysis and Recycling Studiesmentioning
confidence: 70%
See 4 more Smart Citations
“…4 and Table 3 demonstrate clearly that by adding perfluoroalkyl sidearms to the dibenzo-18-crown-6 structure in compounds (14) and (15), the phase transfer catalytic activity is increased significantly, but when alkyl sidearms are attached in compound (11), the catalytic activity only increases moderately compared to dibenzo-18-crown-6 (9). The results also showed that compounds (14) and (15) have essentially the same catalytic activity and so, the length of the perfluoroalkyl group does not affect the catalytic activity in benzotrifluoride. On the other hand, the cis-4,4 0 -dialkylamino crown ether (18) showed extremely poor catalytic activity under the same reaction conditions, whilst the cis-4,4 0 -di(1H,1H-perfluoroalkylamino)-derivatised crown ether (19) had a very similar rate profile to dibenzo-18-crown-6 after 5 h. Presumably, the polarity and solubility of (18) had an important effect on the reaction equilibria constants in benzotrifluoride and (18) may be a more efficient PTC catalyst in an alternative non-fluorinated organic solvent.…”
Section: Phase Transfer Catalysis and Recycling Studiesmentioning
confidence: 70%
“…Initially, when the reaction was carried out with the supported catalyst (14) in benzotrifluoride at 110 8C, the conversion was only 30% after 5 h. In comparison to the homogeneous reaction, which was complete after 3 h, this result demonstrated the reduced activity of the supported catalyst (14). The iodide displacement reaction was then carried out in ethyl acetate and THF in order to evaluate the effect of a different solvent environment on the reactivity of the supported catalyst.…”
Section: Phase Transfer Catalysis and Recycling Studiesmentioning
confidence: 95%
See 3 more Smart Citations